Planning beyond 2000 - Allmendinger, Philip; Chapman, Michael (John Wiley & Sons, 1999)
Providing a complete and comprehensive overview of planning issues, policy and theory in the UK, it goes on to assess the state of current planning theory, its revival in the 1990s and what questions theorists will need to address over the next 15 years.